LIMITTING REDUCTION RATIO SEBAGAI BATAS REDUKSI UKURAN MATERIAL PADA SINGLE TOGGLE JAW CRUSHER - Sumarjono, Erry; Budi, M. Sri Prasetyo; Sukamto, Untung (KURVATEK, 2025)
Reduction Ratio (RR) can be used to estimate the size of product that can be produced by a crusher. The reduction ratio can be calculated in several ways. One calculation that can be done is calculating the Limitting Reduction Ratio (LRR). Limiting Reduction Ratio is a comparison between the largest feed size and the largest product size. This research aims to calculate the Limiting Reduction Ratio in clay stone crushing operations for 30 samples, which was carried out on a laboratory scale, using a single toggle jaw crusher type crusher. Crushed products are separated by hand sieving sizes +4#, 10#, 20#, 40#, 60#,100#, 200#. The research results show that the percentage of crushed products produced is still found in the largest sieve size, namely 4#, with an average amount of 52.33%. The largest feed size ranges from 24 mm to 27 mm and the largest product size ranges from 4 mm to 6 mm. The relationship between total feed weight and total product weight can be expressed in the equation Y = 0.5229 X and R2 = 0.9228, while the relationship between the largest feed size and the largest product size is expressed in the equation Y = 0.2044 X and R2 = 0.9761. The calculation of the limiting reduction ratio ranges from 4.2 to 6.8, with an average value of 5.02. Keywords: Crushing, Jaw Crusher, Mineral Processing, Reduction Ratio, Reduksi